Pengaruh Kualitas Layanan dan Kepercayaan Terhadap Minat Beli dan Loyalitas Pelanggan pada Minuman Chatime di Daerah Bekasi Utara - Hernandes, Frisco; Ali, Hapzi (Siber Nusantara Publisher, 2024)
The research carried out aims to determine simultaneously and partially the independent variables, namely Service Quality and Trust, the dependent variables, namely Purchase Interest and Customer Loyalty. This research was conducted in Chatime, North Bekasi area. The method used in this research is a quantitative method, where this research uses the Purposive Sampling technique using the Hair formula to determine how to take samples. The population in this study were all Chatime customers in the North Bekasi area, totaling 84 respondents. Based on the research results, it shows that the Service Quality variable on Purchase Interest provides a path coefficient value of 0.196 and has a p- value of 0.045 and a T-statistic value of 2.008 (T-statistic > T table 1.96). Shows that service quality influences purchasing interest. So it can be stated that hypothesis 4 is supported. Because the T-statistic value meets the requirements, namely T-statistic > T-table 1.96 and Purchase Interest on Customer Loyalty, it gives a path coefficient value of 0.293 and has a p-value of 0.026 and a T- statistic value of 2.230 (T-statistic < T table 1.96). Showing that, purchasing interest has an effect on customer loyalty, it can be stated that hypothesis 5 is supported. Because the T-statistic value does not meet the requirements, namely T-statistic > T-table 1.96